Methane flux and gas hydrate accumulations in the Sea of Okhotsk and their ecological aspects - Sokolova, N.L.; Telegin, Yu. A.; Obzhirov, A.I. (Vietnam Journal of Earth Sciences, 2021)
Methane is one of the important representatives of the organic substances in the atmosphere (for example, an increase of methane content in the atmosphere can affect enhancing the greenhouse effect). Gas hydrates are an essential part of links in the methane cycle and the accompanying fluxes of other gases. The research object in this paper is the Sea of Okhotsk, where gas hydrate fields and active submarine gas discharge areas were found. The study of methane fluxes is relevant both for the Sea of Okhotsk and the World Ocean. From 1984 to 2015, the background and anomalous methane fields were explored in the Sea of Okhotsk as a result of gas geochemical research carried out by scientists of the Gasgeochemistry Laboratory (POI FEB RAS). The flux of natural gas became stronger from the sources to the seafloor, from the seafloor to the water, and, finally, to the atmosphere due to renew of fault zones. Moreover, the amount of methane vents on the Sakhalin slope has increased from 2-3 vents to more than 400. The most representative hydroacoustic anomalies “flares” mapped direct methods study methane hydrates. The received outcomes indicate the urgency of the study of methane fluxes and the formation-dissociation mechanism of gas hydrates, and the influence of natural gas from hydrocarbon sources on the environment.